OP0064 Clefs de dos: a unique pare-led video program to improve coping skills of people living with axial spondyloarthritis. (15th June 2017) - Beauvais, C; Sordet, C; Leboime, A; Vandame, D; Saadoun, C; Genin, G; Gerald, F
Abstract : Background: Diagnosis of axial spondyloarthritis (axSpA) is often delayed, with an estimated time to diagnosis of 6 years, 1 leading to patient (pt) anxiety and difficulties in coping with daily life. Many fears and beliefs have been identified, 2 including unpredictability of the disease course and concerns for the future. A survey revealed that 61% of pts want to share such experiences with other pts. 3 Objectives: The goals were to: 1) create a video program to help pts share experiences and promote coping strategies; 2) establish the program on the internet and social networks; 3) assess the usefulness of the program for pts and healthcare professionals (HCPs). Methods: Clefs de dos is a national French program initiated in 2015. It is led by a pt organisation, ACS-France (Action Contre les Spondyloarthropathies), Catalpa (conducted interviews, made visuals) and UCB Pharma (co-creation and promotion). Pts with axSpA were recruited by ACS on a voluntary basis to participate in focus groups; pts were selected according to their level of disease acceptance (denial [Gp1] or acceptance [Gp2]). 4 steps were planned: 1) Gp1 focus group interviews to collect feelings, words and voices; 2) Gp2 interviews to describe the pt pathway and stages in the process of disease acceptance; 3) face-to-face Gp1+Gp2 meetings for pts to share their own experiences and confront their own views; 4) rheumatologist interviews to evaluate the impact of pt testimonies on their own practice. Results: 13 axSpA pts (10 Gp1, 3 Gp2) participated, aged 25–65 years (yrs), with 5–17 yrs disease duration; 10 were female. An animated visual was produced using Gp1 pt interviews; analysis revealed feelings of loss prior to diagnosis. Photographs and audio testimonies were used to create 3 documentary portraits of Gp2 pts, illustrating the process of disease acceptance and acquisition of coping skills (Figure). Videos of Gp1+Gp2 meetings emphasised interpersonal help and counselling between pts. 3 rheumatologists participated in step 4. They identified the importance of pt interaction to develop positive strategies, pt perspective and removal of barriers in the physician-pt relationship, and use of videos in self-management programs. By December 2016, >5, 000 people had visited the website (www.clefsdedos.com ), with ∼500 Facebook followers from March–December 2016 (www.facebook.com/Clefsdedos/ reaching ∼30, 000 people via link sharing. Conclusions: Clefs de dos was developed by and for axSpA pts. The program answers unmet needs by sharing pt experiences, particularly in situations of delayed diagnosis and lack of disease acceptance. Online access reflects good acceptability of the program, which can also be used as an educational tool in self-management. The next step is to involve other HCPs (eg. nurses, physiotherapists, psychologists). References: Wendling D. Joint Bone Spine 2014;81(1):6–14. Berenbaum F. PLoS One 2014;9(12):e114350. Bolla G. Presentation O13, SFR 2014; Paris, France. Acknowledgements: The authors acknowledge all patients who participated in the Clefs de dos program, and L Epivent and A Martra for contributions in co-building the communication plan. This program was conducted in partnership with ACS-France and Catalpa, and co-created and funded by UCB Pharma. Disclosure of Interest: C. Beauvais Speakers bureau: UCB Pharma, C. Sordet: None declared, A. Leboime: None declared, D. Vandame Employee of: UCB Pharma, C. Saadoun Employee of: UCB Pharma, G. Genin: None declared, F. Gerald: None declared